What Do We Mean by “Soundscape”? A Functional Description - Grinfeder, Elie; Lorenzi, Christian; Haupert, Sylvain; Sueur, Jérôme (Frontiers in Ecology and Evolution, 2022)
The concept of soundscape was originally coined to study the relationship between humans and their sonic environment. Since then, several definitions of soundscapes have been proposed based on musical, acoustical and ecological perspectives. However, the causal mechanisms that underlie soundscapes have often been overlooked. As a consequence, the term “soundscape” is frequently used in an ambiguous way, alternatively pointing to objective realities or subjective percepts. Through an interdisciplinary review, we identified the main biotic and abiotic factors that condition non-anthropogenic terrestrial soundscapes. A source-filter approach was used to describe sound sources, sound propagation phenomena and receiver’s characteristics. Interdisciplinary information was cross-referenced in order to define relationships between factors, sound sources and filters. Those relationships and the associated references were organized into a functional block diagram. This representation was used to question the different uses and meanings of the soundscape concept found in the literature. Three separate categories were then suggested: distal soundscape, proximal soundscape and perceptual soundscape. Finally, practical examples of these different categories were described, in relation to the diagram. This new systemic approach to soundscapes should help ecoacousticians, bioacousticians, psychoacousticians and environmental managers to better understand soundscapes and protect natural areas in a more significant way.